Job satisfaction as a source of well-being based on consumption emigration in Canada - Terelak, Jan Felicjan; Borkowska, Aleksandra (Studia Psychologica: Theoria et praxis, 2007)
This paper has an empirical character, and concerns looking for a source of well-being by modern populations in job satisfaction. Research included 30 polish consumption emigrants living in Canada (Toronto, Ontario). Control group included 25 Poles living in Poland, who visited for several times western- European countries or USA. Following methods had been used: Minnesota Satisfaction Questionnaire MSQ- Short Form (to measure job satisfaction), Self- Anchoring Scale Hadleya Cantrila (to measure general life satisfaction – cognitive component), P. Boski’s “E” Scale (to measure general life satisfaction – emotional component), J. Czapinski’s “WŻ” Scale (to measure life’s will). It was found that person who is satisfied from his work estimates higher his general life in happiness category. Polish consumption emigrants who are living in Canada do not differ from the polish group living in Poland, although Polish living in their own country were interior more diverse. Job satisfaction do not influence life’s will – the deepest level of wellbeing.